Dari pelarian ke panggilan: Formasi kepemimpinan Musa sebagai paradigma pembentukan pemimpin Kristen masa kini - Napitupulu, Pieter Anggiat (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2025)
Abstract: This article examines the formative process of Moses’ leadership in the Book of Exodus as a paradigm for shaping Christian leaders today. Moses’ transformation from a fugitive to a prophetic leader demonstrates that true leadership does not emerge from human readiness but from God’s formation through suffering, isolation, and spiritual encounter. The narrative highlights the importance of submitting to God’s timing and methods in responding to His call, emphasizing that leadership is not merely about the ability to lead, but about who is being shaped to lead. In today’s context, marked by a crisis of integrity and authenticity, the story of Moses offers a model of leadership rooted in humility, dependence on God, and a willingness to serve. Using a biblical-theological approach, this article reflects that the formation of Christian leaders must be grounded in deep spirituality rather than merely in competence or structural position.